The imposition of corruption criminal acts: handling corruption cases in Indonesia number. 28/PID.SUS.TPK/2020/JKT.PST - Sariat Arifia (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
The imposition of corruption offense in case Number. 28/PID.SUS.TPK/2020/ JKT.PST, where the imposition of the offense of participation in acts of gratification is separated into two categories, namely those who give bribes and those who are bribed. It is unclear how the Judge differentiates those who give bribes and those who are bribed. Thus, the research question is as follows: How is the implementation of participating in corruption cases in accordance with the case judgment number. 28/PID.SUS.TPK/2020/JKT.PST? Second, how is criminal behavior in corruption instances regulated in Indonesia? The research method employed is normative juridical, which means that it is based on an examination of pertinent laws and regulations. The study's conclusions include the absence of reason and logic in the judges' deliberations and decisions regarding the classification of bribery in case number. 28/PID.SUS.TPK/2020/ JKT.PST. Second, there is a legal vacuum or loophole in which no rules have a clear formula for classifying those who give bribes or those who are bribed. According to these two results, the regulation of participation in criminal acts of corruption still need conceptual and technical refinement in the future